Directive Speech Act used by the Main Characters in Barbie and the Three Musketeers Movie - Ananda Anisa Anadhiva Anadhiva; Nuning Yudhi Prasetyani; Binti Qani’ah (CV. Rustam, 2024)
This study explored the use of directive speech acts by the main characters in the film Barbie and the Three Musketeers. The primary objective was to identify and analyze the types of directive speech acts employed, drawing on Searle's theory. A descriptive qualitative approach was utilized to dissect the dialogue in the film, which revealed nine distinct types of directive speech acts: requesting (12 instances), ordering (11 instances), commanding (8 instances), advising (7 instances), challenging (5 instances), permitting (4 instances), inviting (4 instances), begging (4 instances), and prohibiting (2 instances). The analysis highlighted how these speech acts were integral to the characters' interactions and their quest to become female musketeers, a role traditionally seen as male-dominated. The directive speech acts reflected the characters' emotions and propelled the narrative forward, illustrating their determination, resourcefulness, and collaboration. Challenging societal stereotypes, the characters used directive speech acts to assert their agency and challenged the notion that musketeering was exclusively for men. This study contributes to a deeper understanding of how language functioned in animated films to shape character development and advance thematic elements.